The Hegemony of Hedonism Lifestyle of Sales Promotion Girl (SPG) in Indah Hanaco’s `The Curse Of Beauty` - Fiqih Aisyatul Farokhah; Sri Kusumo Habsari; Mugijatna Mugijatna (Universitas Muhammadiyah Semarang, 2018)
The mainstream of pop literature has developed fast now. It tells the lifestyle of urban society which is too glamour, consumptive and hedonistic. In this era of industrialization and capitalism phase influence them to trap in luxurious habit. It does not only affect the upper class but also thepoor society. The activities such shopping branded stuff, hanging out in the mall, changing the up to date mobile phone only for chatting and playing social media become the addiction. Unsurprisingly, there are many people do everything to make it come true. They never realize, they are the victim of this fake light life. One of them is Sales Promotion Girl (SPG) workers. The hedonism lifestyle has hegemonized their life until they take the risk to come in this Job. They do not know, their body has been exchanged by hedonism lifestyle. This phenomenon does not only happen in the reality but also in the pop literature as like Indah Hanaco‟s work. Her novel theCurse of Beauty tells about the true lifestyle of SPG that is trapped to hedonism lifestyle, therefore, they are willing to do sell their precious life to the prostitution world. This paper aims to show the form of SPG‟s hedonism lifestyle in this novel. Then, it tries to find the causes of thosehabits until they are willing to sell their body. Finally, it comes to the purpose of the author to take this situation become the pop literature.